Transition metal-free electrocatalytic halodeborylation of arylboronic acids with metal halides MX (X = I, Br) to synthesize aryl halides. Issue 3 (16th January 2020) - Fu, Zhengjiang; Hao, Guangguo; Fu, Yaping; He, Dongdong; Tuo, Xun; Guo, Shengmei; Cai, Hu
Abstract : An efficient and regioselective ipso -halogenation of diverse arylboronic acids with metal halide salts MX (X = I, Br) has been well established under electrochemical conditions. Abstract : An efficient and regioselective ipso -halogenation of diverse arylboronic acids with metal halide salts MX (X = I, Br) has been well established under electrochemical conditions. A gram-scale reaction has been performed to evaluate the applicability of the protocol. Cyclic voltammetry experiments indicated that the halide anion was oxidized prior to the arylboronic acid substrate under standard conditions.